2015
DOI: 10.1177/1475240915573136
|View full text |Cite
|
Sign up to set email alerts
|

Home and away: An inquiry into home-based and overseas teacher perceptions regarding international schools

Abstract: The world of international schools is expanding, fuelled in part by globalisation and the ease with which employees can relocate across the globe as they seek new employment opportunities. As these mobile families relocate overseas, international schools provide an education for their children which may offer a curriculum based on a common and transferable syllabus, similar to one they experienced at home. The research on which this article is based presents a picture not only of teaching in the United Kingdom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 5 publications
3
7
0
Order By: Relevance
“…This finding confirms media reports and other research findings that suggest that UK teachers are leaving the UK due to their frustrations with practice there (Hrycak, 2015; Richardson, 2016). Similarly, teachers on local contracts emphasized the higher level of professionalism and collegiality in international schools that was lacking in local schools in Kuwait.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…This finding confirms media reports and other research findings that suggest that UK teachers are leaving the UK due to their frustrations with practice there (Hrycak, 2015; Richardson, 2016). Similarly, teachers on local contracts emphasized the higher level of professionalism and collegiality in international schools that was lacking in local schools in Kuwait.…”
Section: Resultssupporting
confidence: 89%
“…Our findings suggest that for teachers on both overseas and local contracts, the reason for working in an international school is largely financial, confirming findings from previous research by Hrycak (2015); in particular, those leaving the UK spoke about “the bottom line” and “worsening work conditions due to poor student behaviour” as noted by one teacher. Other UK leavers spoke of being “directly impacted by the 2008 economic crisis” and commented that international schools seemed attractive then because they offered beneficial packages including, for instance, higher salaries, accommodation, health insurance, ease of traveling back to their country of origin, and free or discounted education for their children.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Savva argues that the main reasons teachers seek out international schools over others are related to travel, financial incentives, and a better life (Savva, 2015), to which Hrycak (2015) added focused students, supportive school parents, lighter workloads and smaller classes. Once teachers decide to teach internationally, Halicioglu (2015) has suggested that interculturally competent teachers have an advantage because they are more capable of acclimatising to international schools, while Hirsch (2016) has noted that teachers who are not interculturally competent or have not experienced diversity training are less likely to be effective in the classroom.…”
Section: Administratorsmentioning
confidence: 99%
“…1 This stance makes international education 2 ideologically attractive to some teachers, who see it as a progressive and timely educational field that is imbued with open-mindedness and a spirit of pluralism adapted to a globalised world. At the same time, professional autonomy and the opportunity to travel and to deepen intercultural understanding reinforce the choice of international teaching as an attractive pathway for people eager to embark on fresh challenges both in their professional and personal lives (Savva 2013;Hrycak 2015). In this respect, international teaching may not only have an intrinsic value for the ideals that are associated with the profession, 3 but can also give the impression of a type of 'lifestyle migration', a privileged form of mobility driven by globalisation, individualisation, increased ease of movement, work-related flexibility, and increases in relative global wealth.…”
Section: Introductionmentioning
confidence: 99%